Rational Control of the Selectivity of a Ruthenium Catalyst for Hydrogenation of 4‐Nitrostyrene by Strain Regulation. Issue 39 (15th August 2017) - Mao, Junjie; Chen, Wenxing; Sun, Wenming; Chen, Zheng; Pei, Jiajing; He, Dongsheng; Lv, Chunlin; Wang, Dingsheng; Li, Yadong
Abstract: Tuning the selectivity of metal catalysts is of paramount importance yet a great challenge. A new strategy to effectively control the selectivity of metal catalysts, by tuning the lattice strain, is reported. A certain amount of Co atoms is introduced into Ru catalysts to compress the Ru lattice, as confirmed by aberration‐corrected high‐resolution transmission electron microscopy (HRTEM) and X‐ray absorption fine structure (XAFS) measurements. We discover that the lattice strain of Ru catalysts can greatly affect their selectivity, and Ru with 3 % lattice compression exhibits extremely high catalytic selectivity for hydrogenation of 4‐nitrostyrene to 4‐aminostyrene compared to pristine Ru (99 % vs. 66 %). Theoretical studies confirm that the optimized lateral compressive strain facilitates hydrogenation of the nitro group but impedes the hydrogenation of the vinyl group. This study provides a new guideline for designing metal catalysts with high selectivity. Abstract : Taking the strain : Introducing Co atoms into a Ru catalyst compressed the Ru lattice strain, thus further affecting catalytic selectivity for hydrogenation of 4‐nitrostyrene to 4‐aminostyrene. Theoretical studies reveal that the optimized lateral compressive strain facilitates hydrogenation of the nitro group but impedes the hydrogenation of the vinyl group.